A new arsenal of polyphenols to make Parkinson's disease extinct: HPLC-MS/MS profiling, very interesting MAO-B inhibitory activity and antioxidant activity of Otostegia fruticosa. Issue 23 (1st December 2022) - Al-Madhagy, Somaia A.; Gad, Sameh S.; Mostafa, Eman S.; Angeloni, Simone; Saad, Muhammed A.; Sabry, Omar M.; Caprioli, Giovani; El-Hawary, Seham S.
Abstract: Fifteen compounds belong to phenolic acids, derivatives of phenolic acids, iridoids, xanthones and flavonoids were characterized in the methanolic extract of Otostegia fruticosa leaves using HPLC-MS/MS. Extract has been also investigated for its MAO-B inhibitory activity, antioxidant activity, total phenolic and total flavonoid content. The extract exhibited interesting MAO-B inhibitory activity (IC50; 2.24 ± 0.08) compared to the reference compound selegiline (0.55 ± 0.02 µg/mL). It also showed a potent antioxidant activity proven in both DPPH and ORAC assay methods. The extract showed an IC50 of 3.64 ± 1.22 µg/mL in the DPPH test which was significantly lower than that of the standard ascorbic acid which attained an IC50 of 18.3 ± 1.41 µg/mL. Moreover, in the oxygen radical absorbance capacity assay (ORAC) the extract showed a decline in the IC50 to 3.48 ± 1.16 µg/mL as compared to the standard Trolox which exhibited an IC50 of 27.0 ± 13.41. Graphical Abstract: UF0001